2018
DOI: 10.3390/met8121007
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Characterization of the Transition Zone of 9%Ni Steel Cladded with Ni-Based Superalloy 625 by GTAW-HW

Abstract: 9%Ni steel was recently used for the first time in the field of injection unit (IU) for the injection of CO2 into oil wells. Because such steels are operated in H2S medium and are susceptible to sulfide stress cracking, their pipes are cladded with Ni-based superalloy 625 by using gas tungsten arc welding with a hot wire to prevent this phenomenon from occurring. The transition zone of substrate/clad can have high hardness and low toughness, and promote failure of the component during service; therefore, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 58 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…In order to investigate the influence of alloying elements on the microstructure, Al, Ti, and Nb were added to Colmonoy 56 PTA in small amounts according to Table 2. The alloy modifications were selected on the basis of [8,18,19]. Further investigations are conducted into the influence of the additions on machinability because this correlates directly with the microstructure.…”
Section: Materials Usedmentioning
confidence: 99%
“…In order to investigate the influence of alloying elements on the microstructure, Al, Ti, and Nb were added to Colmonoy 56 PTA in small amounts according to Table 2. The alloy modifications were selected on the basis of [8,18,19]. Further investigations are conducted into the influence of the additions on machinability because this correlates directly with the microstructure.…”
Section: Materials Usedmentioning
confidence: 99%
“…Previous research by Nelson et al [65] has proposed that the transformation of ferrite (δ-γ) allotropic phases in the coarse-grain heat-affected zone (CGHAZ) during cooling is a critical prerequisite for the formation of type-II boundaries in structural steel. Recently, Farias et al [39] postulated that the interface between the substrate and the clad is mobile and can induce projection of the CGHAZ into the clad during cooling, resulting in the formation of type-II boundaries. It is worth mentioning that the type-II boundary was only observed in a small section of the TZ.…”
Section: Transition Zone (Tz)mentioning
confidence: 99%
“…In the laser cladding on Ni-steel with stainless steel AISI 304 research conducted by Wu et al [38], it was reported that the TZ exhibited a type-I boundary and had harder martensite phases. However, during the cladding of this same Ni-steel with a Ni-based alloy, by a different technique, hot-wire gas tungsten arc welding (GTAW-HW), Farias et al [39] reported the observation of both type-I and type-II boundaries in the TZ without SSCC. It can be inferred from these studies that the resulting microstructure of the TZ and its characteristics vary depending on the cladding method used for material deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic works on cladding nickel alloys using hot wire technology were reported. 33,34 Literature on HWGTAW of nickel and its alloys is limited in existing literature. Therefore, this research work was undertaken to explore the microstructure and the tensile behavior of nickel tubes joined by HWGTAW and examined the role of wire feed rate in particular.…”
Section: Introductionmentioning
confidence: 99%